Evaluation of the village development index as an effort to provide the right policy intervention - Muhammad Roisul Basyar; Anggraeny Puspaningtyas; Vivtania Salsa Bella; Dimas Kurnia Firmansyah (Universitas Islam Malang, 2022)
The change in the paradigm of village development from